The challenge of ovarian tissue culture: 2D versus 3D culture - Ana Sofia Pais; Sandra Reis; Mafalda Laranjo; Francisco Caramelo; Fátima Silva; Maria Filomena Botelho; Teresa Almeida-Santos (BMC, 2021)
Abstract Background Cryopreservation of ovarian tissue is a powerful technique for preserving female fertility, as it can restore fertility and endocrine function. To increase the longevity of the transplant and decrease the risk of reimplantation of neoplastic cells, several studies have been carried out with culture of ovarian tissue. The aim of this study was to compare a conventional (2D) culture with an alginate matrix three-dimensional (3D) model for ovarian tissue culture. Results The ovarian tissue culture within the alginate matrix (3D) was similar to 2D culture, regarding follicular density and cell apoptosis in follicles and stroma. The proliferation rate remained stable in both models for follicles, but for stromal cell proliferation it decreased only in 3D culture (p = 0.001). At 24 h of culture, cytotoxicity was lower in the 3D model (p = 0.006). As culture time increased, cytotoxicity seemed similar. Degradation of the tissue was suggested by the histological score analysis of tissue morphology after 72 h of culture. Tissue injury was greater (p = 0.01) in 3D culture due to higher interstitial oedema (p = 0.017) and tissue necrosis (p = 0.035). Conclusion According to our results, 3D culture of ovarian tissue has no advantage over 2Dculture; it is more time consuming and difficult to perform and has worse reproducibility.